Disinformation: exploring the nexus between politics and technology in Nigeria - Olaniran, Samuel (University of the Witwatersrand, Johannesburg, 2022)
Over the past decade, disinformation and social media hoaxes have evolved from a nuisance into a high-stake information war, exploiting weaknesses in our online information ecosystem. Although social media has the potential to strengthen democratic processes, there is increasing evidence of malicious actors polluting Nigeria’s information ecosystem during elections. Misleading narratives targeting candidates and political parties were picked up, liked, shared, and retweeted by thousands of other users during the 2019 presidential election campaign. Rooted in the theoretical lens of centre/periphery dynamics and equalizing and normalizing hypothesis, this study examines the networked nature of disinformation by identifying instigators, techniques, and motivations for spreading manipulated information around elections. While providing valuable data-driven insights drawn from a computational analysis of over 3 million tweets and a critical blend of qualitative framework, this study analyses the human agency and motivations behind online disinformation. The spread of falsities is coordinated in a way that “ordinary users” unknowingly become “unwitting agents” as “sincere activists” of concerted influence operations, a participatory culture that amplifies disinformation and propaganda. Agents’ participation in the “nairainfluenzer” industry is motivated by factors such ethnic and religious sentiments, poor economy, and low trust in news media. These findings broaden the perspective for examining top-down, orchestrated work as well as other types of coordination that stress how election-related disinformation heightens centre/periphery power dynamics. It further emphasizes that the systematic production and amplification of disinformation on Twitter represents a universal online behaviour not common “emotional-periphery” states.
Keywords: Disinformation; Twitter; Participatory Culture; Techno-politics; UCTD; SDG-17: Partnerships for the goals